Community Empowerment Through Social Entrepreneurship Implementation : A Literature Review - Hapsari, Rosma Titis; Yayan Hendayana (Dinasti International Journal of Management Science, 2024)
The problems with social entrepreneurship are scarce resources, ignorance, and inadequate government assistance. The literature review strategy was used in this investigation. The study's findings suggest that social entrepreneurship training and network building help communities build the information and abilities needed to grow their enterprises, as well as dependable relationships and increased access to resources. Through social entrepreneurship, communities can also become more financially independent, make more money, and become economically self-sufficient.